Criminalization of Lesbian, Gay, Bisexual and Transgender (LGBT) Behavior in Indonesia from the Perspectives of Maqashid Shari'ah and Utilitarianism - Al Fikri, Badrus Zaman; Chanifah, Nur; Noerdajasakti, Setiawan (International Journal of Business, Law, and Education, 2025)
This study aims to analyze the formulation of legal regulation for the criminalization of LGBT sexual behaviour in Indonesia through the perspectives of Maqashid Syari'ah and Utilitarianism. In a country with a Muslim-majority population, the LGBT phenomenon frequently raises a conflict between human rights protection and religious values. Using a normative juridical approach, this study examines legislation, legal theories, and relevant secondary data. Findings indicate that there is no explicit national regulation criminalizing LGBT behaviour. The Maqashid Syari'ah perspective emphasizes the protection of five fundamental principles: religion, life, intellect, lineage, and property. Meanwhile, Jeremy Bentham's Utilitarianism asserts that legal policy should maximize societal benefit. The study concludes that integrating these two approaches provides a balanced foundation for criminal policy formulation that upholds moral values and public interest without compromising justice and human rights.